Incorporation of a Non‐Natural Arginine Analogue into a Cyclic Peptide Leads to Formation of Positively Charged Nanofibers Capable of Gene Transfection. (27th November 2015) - Li, Mao; Ehlers, Martin; Schlesiger, Stefanie; Zellermann, Elio; Knauer, Shirley K.; Schmuck, Carsten
Abstract: Functionalization of the tetracationic cyclic peptide (Ka)4 with a single guanidiniocarbonyl pyrrole (GCP) moiety, a weakly basic but highly efficient arginine analogue, completely alters the self‐assembly properties of the peptide. In contrast to the nonfunctionalized peptide2, which does not self‐assemble, GCP‐containing peptide1 forms cationic nanofibers of micrometer length. These aggregates are efficient gene transfection vectors. DNA binds to their cationic surface and is efficiently delivered into cells.